Bilateral maxillary first molars with Vertucci type I canal anatomy in a Saudi patient: A case report on endodontic management and outcome assessment using cone-beam computed tomography - Kholod Khalil Al-Manei (Saudi Endodontic Journal, 2026)
Abstract Effective endodontic therapy relies on thorough clinical and radiographic assessment of the tooth’s internal anatomy. A single-root, single-canal (Vertucci type I) configuration is uncommon in maxillary first molars. This case report details the endodontic management of bilateral maxillary first molars with Vertucci type I canal configuration in a Saudi patient. An 11-year-old girl in good health was referred for treatment of carious maxillary first molars. Clinical examination revealed deep caries, no tenderness to percussion, normal probing depths, and mobility in both molars. Pulp tests were negative for the right molar, and the left showed a nonlingering response. Radiographs showed an unusual canal anatomy (Vertucci type I). The right molar was diagnosed with pulp necrosis and normal periapical tissue, while the left had reversible pulpitis with normal periapical tissue. Root canal therapy was performed on the right molar and vital pulp therapy with indirect pulp capping on the left. The 5-year follow-up confirmed successful outcomes based on clinical, radiographic, and cone-beam computed tomography assessments. This report aims to increase clinicians’ awareness of this rare root canal anatomy.